Taxation and Incentive in Mobilization - Cooper, Gershon (Quarterly Journal of Economics, 1952)
I. Introduction, 43. — II. The influence of income taxation upon hours of work, 45. — III. Summary and conclusion, 63. — Appendix, 65.